Carbon production at shallow‐water artificial reef ecosystems relies on water column primary productivity - Traci Erin Cox; Kelly S. Boyle; Mark A. Albins; Sean P. Powers; Just Cebrian (Limnology and Oceanography, 2025)
The attraction‐production continuum in fishery management centers on the extent to which artificial reefs increase fish production or whether they simply redistribute fish. Reef systems could produce carbon to support growth of higher trophic levels. Therefore, we aimed to understand carbon flows at lower trophic levels on shallow‐water (11 m) artificial reefs within a region which hosts an extensive artificial reef network. We described benthic communities and quantified changes in oxygen content within in situ enclosures to assess reef, sediment, and water‐column community metabolism. We tested spatial and temporal differences in metrics by repeatedly sampling at three sites across two seasons for 2 yrs. Suspension feeders were abundant on reef surfaces and these communities were often heterotrophic. In sediments, lancelets, amphipods, and bivalves were scarcer adjacent to the reef (2 m) and more numerous 20 m away. Infauna communities at adjacent reefs were significantly dissimilar, suggesting biotic (e.g., predation) and, or abiotic (e.g., sand scour) conditions cause large differences in infauna communities near reefs. Sediment and water‐column communities were mostly autotrophic and net productivity did not consistently increase or decrease with distance from the reef. Metabolic metrics were often best explained by temporal intervals and site. The integrated system was autotrophic in 9 out of 11 instances where reef, sediment, and water‐column contributed −0.46 to 0.27, −14.8 to 66.8, and 33.5% to 91.4% respectively to net system productivity. When planning artificial reef deployment projects with heterotrophic reefs, managers should ensure ample water‐column space is provisioned to support them trophically.